Entrepreneurship education enhances the character of higher student; bibliometric study - Amir, Ja’far; Mulyati, Mulyati; Ahmadi, Slamet (Trigin Publisher, 2024)
A Bibliometric method could facilitate a comprehensive and subjective evaluation of current education of entrepreneurship, based on several reasearches. Entrepreneurship rapidly became the most popular theme after Pandemic COVID-19. So many aspects to be considered when formulating entrepreneurship education. From this paper finding, by leveraging bibliometric of Scopus metadata it reveals and recommended to elert in tecnopreneurship and biotechnology. It will encourage higher students to get their whole understanding and impacted to increase intention to be an entrepreneur. The characteristics of millennial entrepreneurs are entrepreneurial intention, creative industry, entreprenereul education, self-efficacy, start-up, innovation, sosial entrepreneurship and digital entrepreneurship. Keep consistent due entrepreneurship education. It will induce entrepreneurial spirit